PENERJEMAHAN KATA FATIS BAHASA INDONESIA KE DALAM BAHASA JEPANG PADA WEBTOON MY PRE – WEDDING - Septia Eka Juniati; Hermandra Hermandra; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research discuses about translation of Indonesian phatic words into Japanes. On this research, writer using descriptive qualitative method with phatic theory by Kridalaksana (1986) and translation method by Newmark (1988). After collecting data on the webtoon, writer found 17 types of phatic words, it’s ah, deh, dong, kan, kek, kok, -lah, lho, nah, pun, sih, toh, ya, yah, ayo, halo and selamat. The results of this research, not all Indonesian phatic words are translated into phatic word in Japanese, because in Japanese there is no class of phatic word like Indonesian language. Translation tends to use communicative translation methods ehich only find the right equivalent in Japanese according to the context of the sentence and structure of the Japanese language.Key Words: Translation, Phatic Word, Webtoon.